Channel-Slot Aggregation Diversity Based Slot Reservation Scheme for Cognitive Radio Ad Hoc Networks - S. M. Kamruzzaman; Abdullah Alghamdi; Abdulhameed Alelaiwi; Mohammad Mehedi Hassan (International Journal of Distributed Sensor Networks, 2014)
In cognitive radio (CR) ad hoc networks, spectrum efficiency and energy efficiency are vitally important because spectrum availability is opportunistic in nature and mobile CR nodes usually have limited energy. Aiming to improve network throughput along with improving spectrum and energy efficiencies, this paper proposes a channel-slot aggregation diversity based slot reservation (CADSR) scheme by which each CR node can utilize multiple slots in different channels simultaneously and efficiently utilize the power control mechanism with only a single CR transceiver. The proposed scheme dynamically assigns channel-slots to CR nodes using the diversity technique according to the topology density of the network and the bandwidth requirement, allowing CR nodes to join and leave the network at any time in a distributed way. A dynamic frame length expansion and shrinking scheme has also been introduced that improves the slot utilization. Extensive simulation results show that the proposed mechanism achieves significant performance improvement in network throughput, energy efficiency, and end-to-end delay.